Study of liver cirrhosis over ten consecutive years in Southern China - Wang, Xing (Baishideng Publishing Group Inc, 2014)
AIM: To investigate the etiology and complications of liver cirrhosis (LC) in Southern China. METHODS: In this retrospective, cross-sectional study, we identified cases of liver cirrhosis admitted between January 2001 to December 2010 and reviewed the medical records. Patient demographics, etiologies and complications were collected, and etiological changes were illustrated by consecutive years and within two time periods (2001-2005 and 2006-2010). All results were expressed as the mean ± SD or as a percentage. The χ(2) test or Student’s t-test was used to analyze the differences in age, gender, and etiological distribution, and one-way analysis of variance was applied to estimate the trends in etiological changes. We analyzed the relationship between the etiologies and complications using unconditioned logistic regression, and the risk of upper gastrointestinal bleeding (UGIB) and hepatocellular carcinoma (HCC) in the major etiological groups was evaluated as ORs. A P value less than 0.05 was considered significant. Statistical computation was performed using SPSS 17.0 software. RESULTS: In this study, we identified 6719 (83.16%) male patients and 1361 (16.84%) female patients. The average age of all of the patients was 50.5 years at the time of diagnosis. The distribution of etiological agents was as follows: viral hepatitis, 80.62% [hepatitis B virus (HBV) 77.22%, hepatitis C virus (HCV) 2.80%, (HBV + HCV) 0.58%]; alcohol, 5.68%; mixed etiology, 4.95%; cryptogenic, 2.93%; and autoimmune hepatitis, 2.03%; whereas the other included etiologies accounted for less than 4% of the total. Infantile hepatitis syndrome LC patients were the youngest (2.5 years of age), followed by the metabolic LC group (27.2 years of age). Viral hepatitis, alcohol, and mixed etiology were more prevalent in the male group, whereas autoimmune diseases, cryptogenic cirrhosis, and metabolic diseases were more prevalent in the female group. When comparing the etiological distribution in 2001-2005 with that in 2006-2010, the proportion of viral hepatitis decreased from 84.7% to 78.3% (P < 0.001), and the proportion of HBV-induced LC also decreased from 81.9% to 74.6% (P < 0.001). The incidence of mixed etiology, cryptogenic cirrhosis, and autoimmune diseases increased by 3.1% (P < 0.001), 0.5% (P = 0.158), and 1.3% (P < 0.001), respectively. Alcohol-induced LC remained relatively steady over the 10-year period. The ORs of the development of UGIB between HBV and other major etiologies were as follows: HCV, 1.07; alcohol, 1.89; autoimmune, 0.90; mixed etiology, 0.83; and cryptogenic, 1.76. The ORs of the occurrence of HCC between HBV and other major etiologies were as follows: HCV, 0.54; alcohol, 0.16; autoimmune, 0.05; mixed etiology, 0.58; and cryptogenic, 0.60. CONCLUSION: The major etiology of liver cirrhosis in Southern China is viral hepatitis. However, the proportions of viral hepatitis and HBV are gradually decreasing. Alcoholic LC patients exhibit a greater risk of experiencing UGIB, and HBV LC patients may have a greater risk of HCC.